Watching or Listening: How Visual and Verbal Information Contribute to Learning a Complex Dance Phrase - Bläsing, Bettina E.; Coogan, Jenny; Biondi, José; Schack, Thomas (Frontiers in Psychology, 2018)
While learning from observation is generally regarded as major learning mode for motor actions, evidence from dance practice suggests that learning dance movement through verbal instruction might provide a promising way to support dancers’ individual interpretation of and identification with the movement material. In this multidisciplinary project, we conducted a study on the learning of dance movement through two modalities, observation of a human model in a video clip and listening to the audio-recording of a verbal movement instruction. Eighteen 2nd year dance students learned two dance phrases, one from observation and one from verbal instruction, and were video-recorded performing the learned material. In a second learning step, they were presented the complementary information from the other modality, and their performance was recorded again. A third recording was carried out in a retention test ten days after learning. Completeness scores representing the recall of the dance phrases, expert ratings addressing the performance quality and questionnaires reflecting the participants’ personal impressions were used to evaluate and compare the performance at different stages of the learning process. Results show that learning from observation results in better learning outcomes in terms of both recall and approximation of the model phrase, whereas individual interpretation of the learned movement material was rated equally good after initially verbal and initially visual learning. According to the questionnaires, participants preferred learning from observation and found it more familiar, which points towards an influence of learning habit caused by common training practice. The findings corroborate that learning dance movement from observation is more beneficial than learning from verbal instruction in general, and add aspects with regards to the process and outcome of multimodal movement learning with potential relevance for dance teaching and training.